Reforming Madrasa Education in Pakistan: Post 9/11 Perspectives - Ms Fatima Sajjad (Journal of Islamic Thought and Civilization, 2013)
Pakistani madrasa has remained a subject of intense academic debate since the tragic events of 9/11 as they were immediately identified as one of the prime suspects. The aim of this paper is to examine the post 9/11 academic discourse on the subject of madrasa reform in Pakistan and identify the various themes presented in them. This paper also seeks to explore the missing perspective in this discourse; the perspective of ulama; the madrasa managers, about the Western demand to reform madrasa. This study is based on qualitative research methods. To evaluate the views of academia, this study relies on a systematic analysis of the post 9/11 discourse on this subject. To find out the views of ulama, in-depth interviews of leading Pakistani ulama belonging to all major schools of thought have been conducted. The study finds that many fears generated by early post 9/11 studies were rejected by the later ones. This study also finds that contrary to the common perception the leading ulama in Pakistan are open to the idea of madrasa reform but they prefer to do itinternally as an ongoing process and not due to outside pressure. This study recommends that in order to resolve the madrasa problem in Pakistan, it is imperative to take into account the ideas and concerns of ulama running them. It is also important to take them on board in the fight against the religious militancy and terrorism in Pakistan.